The universal computer : the road from Leibniz to Turing - Davis, Martin, 1928-2023 (CRC Press, 2018)
"The breathtakingly rapid pace of change in computing makes it easy to overlook the pioneers who began it all. Written by Martin Davis, respected logician and researcher in the theory of computation, The Universal Computer: The Road from Leibniz to Turing explores the fascinating lives, ideas, and discoveries of seven remarkable mathematicians. It tells the stories of the unsung heroes of the computer age - the logicians. New to the thrid edition; much expanded version of the discussion of artificial intelligence and current technology, and the way it confirms the significance of Turing's pencil-and-paper universal machine. Further exploration of the relationship between Kronecker and Cantor."--Provided by publisher